Parameterizacija momenta na krmilnem obroču in optimizacija vodilniškega mehanizma cevne turbine - Krotec, Simon (Strojniški vestnik, 2004)
This paper deals with the guide-vane mechanism of bulb water turbines. The guide-vane mechanism pivots the guide vanes as a function of the water conditions and thus ensures the optimal use of the waterćs energy. The guide-vane mechanism of water turbines is driven by one or two hydraulic cylinders. The dimensions of the complete hydraulic system of a power plant are closely connected with the size of the hydraulic cylinders. These two parameters can have a considerable impact on the price of the guide-vane mechanism as well as the price of the hydraulic equipment and finally on the energy that is put into moving the guide-vane mechanism. In this paper the procedure for the parameterization of the hydraulic torque and the optimization of the guide-vane mechanism is described. For solving this task we used the PTC Pro/Engineer (Pro/E) Wildfire software, and the results are shown graphically.
Keywords: turbine cevne; vodilniki; parameterizacija; optimiranje; cevne turbine